2010
DOI: 10.1007/s00268-010-0923-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy: Solution for Difficult to Heal Acute Wounds? Systematic Review

Abstract: BackgroundHyperbaric oxygen therapy (HBOT) is used to treat various wound types. However, the possible beneficial and harmful effects of HBOT for acute wounds are unclear.MethodsWe undertook a systematic review to evaluate the effectiveness of HBOT compared to other interventions on wound healing and adverse effects in patients with acute wounds. To detect all available randomized controlled trials (RCTs) we searched five relevant databases up to March 2010. Trial selection, quality assessment, data extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Some of the factors influencing HBOT efficiency have not been identified so far -this fact increases the value of the prognostic signs identified by us. Similar results were shown in reports by Cochrane [5,[13][14][15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some of the factors influencing HBOT efficiency have not been identified so far -this fact increases the value of the prognostic signs identified by us. Similar results were shown in reports by Cochrane [5,[13][14][15].…”
Section: Discussionsupporting
confidence: 81%
“…Hyperbaric oxygenation therapy increases cellular pO 2 leading to more intense production of reactive oxygen species (ROS) and reactive nitrogen species (RNS). Thus HBOT can cause improvement in tissue perfusion and oxygenation, and also create sustained conditions for the wound healing process [5]. Hyperbaric oxygenation therapy can constitute a key element in maintaining optimal oxygenation, macroand microcirculation, and nutrition [6].…”
mentioning
confidence: 99%
“…According to the latest assessment, the use of HBOT as adjunct treatment to manage a refractory diabetic wound reduces the risk of major amputation (with an odds ratio of 0.236 and a confidence interval (CI) of 95%: 0.133 -0.418) and improves healing (with an odds ratio of 11.64 and IC 95%: 3.457 -39.196), with a level of evidence "A" (randomised controlled trials) and a grade of recommendation "l" (recommended) (15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that HBOT appears to be effective for the treatment of complex acute wounds (15) . Hyperbaric oxygen improves the effects of acute traumatic ischaemia by means of four mechanisms, namely hyperoxygenation, vasoconstriction, influence on reperfusion, and factors associated with the patient (1) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation